The Outcome of Unilateral Cochlear Implantation in Adults: Speech Recognition, Health-Related Quality of Life and Level of Anxiety and Depression: a One- and Three-Year Follow-Up Study - Bergman, Pia; Lyxell, Björn; Harder, Henrik; Mäki-Torkko, Elina (International Archives of Otorhinolaryngology, 2020)
Introduction Hearing impairment is a common disease worldwide, with a comprehensive impact, and cochlear implantation (CI) is an intervention for profound hearing impairment.Objective To study the outcome one and three years after unilateral CI on hearing, health-related quality of life and level of depression and anxiety, and the correlation between the outcomes. Second, to study whether age, gender, etiology, operated side, residual hearing or cognitive performance can predict the outcome.Methods A prospective longitudinal study including adults with profound postlingual hearing impairment, with respect to hearing (speech recognition), health-related quality of life (Health Utilities Index 3) and level of depression and anxiety (Hospital Anxiety and Depression scale), pre-CI, and one and three years post-CI. The total sample was composed of 40 participants (40% of men), with a mean age of 71 years.Results Speech recognition and the overall health-related quality of life improved one year post-CI (p = 0.000), without correlation (ρ= 0.27), and with no difference three years post-CI. The hearing attribute (in the health-related quality of life instrument) improved one and three years post-CI (p = 0.000). The level of anxiety did not change one and three years post-CI. The level of depression improved one year post-CI (p = 0.036), and deteriorated three years post-CI (p = 0.031). Age, etiology, operated side, residual hearing and cognitive performance did not predict the outcome, but the female gender did significantly improve speech recognition compared with men (p = 0.009).Conclusion The CI significantly improved speech recognition, health-related quality of life and level of depression one year post-CI without mutual correlation, and women performed significantly better than men. There were no further improvements three years post-CI, apart from the hearing attribute.
Keywords: health-related quality of life; cognition; cochlear implantation; anxiety; depression